Soviet Researchers on the Middle East: Ahead of Their Time - I. D. Zvyagelskaya (Vestnik MGIMO-Universiteta, 2019)
In the mid-1950s-1960s the Soviet Orientalists were facing serious challenges. The collapse of the colonial system, the growth of national liberation movements, the entry of new forces that did not fit into the rigid framework of the Communist ideas about the revolutionary process, demanded realistic explanations of what was happening. The article attempts to consider some breakthrough ideas and assessments of historical events in the Middle East put forward by the Soviet experts. The review is primarily based on the publications of Soviet specialists published in the 1970’s. Among those who studied the new trends and tried to explain their further development were Soviet Arabists. At that time their circle was small. Among those who were engaged in political problems of the Arab world, one can name I.P. Belyaev, E.M. Primakov, G.I. Mirsky, A.M. Vasilyev. They had different backgrounds, but all had managed to form in their studies a fairly complete picture of political trends and state-building in the Arab world. Despite the domination of the official dogmas the leading Soviet researchers were able to present a realistic picture of the region, although their «untimely meditations» were presented in a form acceptable to the Communist ideology.The primitive division of society into the bourgeoisie, the proletariat, peasantry and landlords and the hopes for eventual development of communist parties worldwide both did not reflect the realities in the Third World countries and did not leave room for the Soviet Union there. Due to ideological reasons the USSR could not support nationalist movements abroad. Nevertheless, the Soviet leadership passed the first test for the ability to reassess their ideological stereotypes in the early 1950s, when the leaders of the Egyptian revolution turned to the USSR for military assistance. In order to justify the pragmatic choice in favor of supporting the new Arab nationalist leaders, the Soviet scholars developed the concept of three consecutive and co-dependent revolutionary flows: first, the national liberation movement overthrowing the colonial system; second, the world labor movement overthrowing the capitalist system politically; and, third, the world communist movement overthrowing the capitalist system in economic terms.It was also important for the Soviet leaders to explain the orientation of the young decolonized nationalist regimes towards the USSR, without using the argument of just political expediency. Such an explanation was the theory of the non-capitalist path of development or socialist orientation. It posed that capitalism cannot solve any of the problems of developing countries. Their interest in rapid overcoming of backwardness and maintaining national sovereignty cannot be combined with the choice of a capitalist development model. The theory of socialist orientation was based on original ideas of Marxism founders and further developed by Lenin who insisted that economically underdeveloped countries can with the help of the proletariat from advanced countries go directly to socialism bypassing capitalism.The reality of revolutions without the proletariat and the desire to take advantage of the anti-colonial struggle to establish full-scale presence of the USSR in the Middle Eats made the Soviet leadership more tolerant of scientists' attempts to realistically analyze regional trends and developments.For instance, in the Soviet era, politicians were tempted to explain all conflicts in the regions of the Third world, and particularly in the Middle East exclusively by the workings of imperialism. However, Soviet scholars, E.M. Primakov among them, warned in their studies of the dangers of such simplified estimates. Still relevant today also is G. Mirsky’s explanation of the major role the army plays in the politics of the Middle East. He argued that in the traditional societies of the region the army was the only modern, nationwide institution.The works of the Soviet scholars can help better understand contemporary trends. Their studies of driving forces of the revolutions in the Arab world, of the nationalistic regimes, of regional conflicts have not lost their relevance today. They warn the modern generation of researchers against simplistic conclusions, a temptation of politicized assessments and of ignoring the complexity of regional issues.